Review on monograph: “Macroeconomic Stability Of The National Economy” - Oleksii Lyulyov; Oleksandra Karintseva (SocioEconomic Challenges)
The monograph is devoted to topical issues of developing the concept of integration of management and marketing policy for the development of green investment in enterprises. Numerous modern and traditional methods were used in the research, namely: Google Trends tools, Ward agglomeration hierarchical clustering, principal components method, correlation analysis; modified least squares methods FMOLS and DOLS; content analysis and Fishburne’s method; model PLS-PM. The conclusions and hypothesis were confirmed by empirical conclusions using Stata 12 / SE and EViews10. The monograph assesses the level of integrity of the marketing policy of an environmentally responsible enterprise, using content analysis. In addition, the author confirmed the hypothesis that the use of greenwashing reduces the company’s green brand and leads to significant financial and reputational losses. The author has developed a system of principles for green investment management and supplemented it with such specific principles as collaboration (reflecting the characteristics of green investment stakeholder management); dissemination (chain reaction of the appearance of overt / covert socio-ecological-economic effects); convergence (complementarity of green investments, convergence of goals and methods of green investment). The monograph substantiates the specific features of the complex of green investment marketing and the typology of green investment marketing strategies of green investment marketing. The author proposes the concept of 8P marketing of green investments, which takes into account the convergence of basic elements of green and traditional marketing, modern transformations in commodity, credit and stock markets in accordance with the concept of sustainable development, promising trends in eco-oriented consumer and investment needs. It is proved that the growth of trading on the stock exchange in the country is accompanied by the development of the green investment market and increasing the attractiveness of the company among stakeholders. This monograph can be useful for company management, government, students, faculty, researchers, and graduate students.